Очищення стічних вод, що містять нафтопродукти - Семенова, Олена Іванівна; Бублієнко, Наталія Олександрівна; Сулейко, Тетяна Леонідівна; Говоруха, Т. О.; Шилофост, Тетяна Олександрівна (My University, 2012)
Проведено дослідження процесу очищення нафтовмісних стічних вод харчових підприємств: визначено придатність досліджуваних стоків до біологічного окиснення, вивчено інтенсивність споживання кисню муловою сумішшю, встановлена залежність швидкості споживання кисню від концентрації нафтопродуктів, визначено склад основних фракцій нафтових забруднювачів стоків.

Analyzed sources of petroleum wastewater and the danger they may cause the inhabitants of natural waters. The research process of purification of oil wastewater of food businesses. Determined the suitability of the studied wastewater to biological oxidation. Investigated the ability of activated sludge bacteria consume oil wastewater, confirmed that the consumption of petroleum products by microorganisms of activated sludge is less intensive than chemical oxidation of the major organic pollutants of sewage (proteins, fats, carbohydrates). Studied the intensity of oxygen consumption with a mixture of silt, the dependence of rate of oxygen consumption of oil concentration, determined that the concentration of oil in waste water, guided by biochemical purification, should not exceed 70 - 80 mg/dm3 to prevent the suppression of the process of biochemical oxidation. The structure of basic fractions of petroleum pollutant effluent. As a result of mass spectral analysis established that the oil in the waste can be oxidized by specific bacteria belonging to the genera Rhodococcus, Pseudomonas, Mycrococcus i Acinetobacter.
Keywords: нафтовмісні стічні води; біохімічне окиснення; споживання кисню; концентрація нафтопродуктів; oily wastewater; oxygen consumption; concentration of petroleum products; biochemical oxidation; кафедра екології та екоменеджменту